50 Years of Zweifel Olefination: A Transition-Metal-Free Coupling - Armstrong, Roly J.; Aggarwal, Varinder K. (Synthesis, 2017)
The Zweifel olefination is a powerful method for the stereoselective synthesis of alkenes. The reaction proceeds in the absence of a transition-metal catalyst, instead taking place by iodination of vinyl boronate complexes. Pioneering studies into this reaction were reported in 1967 and this short review summarizes developments in the field over the past 50 years. An account of how the Zweifel olefination was modified to enable the coupling of robust and air-stable boronic esters is presented followed by a summary of current state of the art developments in the field, including stereodivergent olefination and alkynylation. Finally, selected applications of the Zweifel olefination in target-oriented synthesis are reviewed.1 Introduction2.1 Zweifel Olefination of Vinyl Boranes2.2 Zweifel Olefination of Vinyl Borinic Esters2.3 Extension to Boronic Esters3.1 Introduction of an Unsubstituted Vinyl Group3.2 Coupling of α-Substituted Vinyl Partners3.3 Syn Elimination4 Zweifel Olefination in Natural Product Synthesis5 Conclusions and Outlook
Keywords: Zweifel olefination; coupling; boronic esters; alkenes; transition-metal-free; enantiospecific